Isolated and combined effects of cold, heat and hypoxia therapies on muscle recovery following exercise-induced muscle damage - Rousse, Y.; Sautillet, B.; Costalat, G.; Brocherie, F.; Millet, G. P. (Sports Medicine, 2025)
The optimisation of muscle recovery from exercise-induced muscle damage (EIMD) is a major issue in sports medicine. This comprehensive review examines the effects of four environmental stressors, including cold (cold therapy), heat (heat therapy), hot-cold alternation (contrast therapy) and reduced oxygen availability (hypoxia therapy), on muscle recovery following EIMD. The analysis of related randomised controlled trials assessed the influences of these stressors on five markers of recovery (muscular performance, joint amplitude, muscle pain, swelling and blood biomarkers). Although cold therapy has been widely studied, the lack of consensus on its application modalities leads to controversial debates regarding its effectiveness for muscle recovery. Heat therapy, particularly hot water immersion, appears to be the most effective method for restoring muscle function. However, the use of local heating techniques is less well understood. Moreover, contrast therapy seems to be promising for reducing swelling post-EIMD; however, the lack of studies and the variety of utilised techniques involving contrast therapy limit conclusions. Finally, local hypoxia, which is elicited by intermittent blood flow restriction, demonstrates potential for reducing inflammation and improving the recovery of muscle function, based on the appropriate application of protocols. By synthesising existing data, this comprehensive review shows that most environmental stress-based therapies can be effective, if the modalities of application—such as dose or frequency—are appropriate. It offers practical recommendations for optimising muscle recovery. This review also highlights the need for further research to refine protocols and better understand the potential synergistic effects of these environmental stress-based interventions.